Green-Synthesis Of Silver Nanoparticles Based On Bioreductor Key Orange Extract As Antibacterial - Fitri Afriani; Susanti Susanti; Fadillah Ramadhani; Muntaz Soraya; Evi.J Evi.J (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
Silver nanoparticles are nano-sized particles ranging from 1-100 nm which are commonly used as antifungal and antibacterial agents in various products. In this study, silver nanoparticles were synthesized from a natural bioreductant, namely key orange peel extract. The silver nanoparticle phase which was successfully synthesized and then XRD test was carried out was cubic in shape with the highest peak at 2θ : 38.1959˚; 44.4038˚; 64.5491˚ The lattice parameter of silver nanoparticles is a=b=c= 4.0861 . The resulting crystal structure of silver nanoparticles is cubic with a crystallite size of 39.84 nm, in addition to XRD test, XRF test was conducted to determine the main constituent components of silver nanoparticles, while the main component of synthesized silver nanoparticles was Ag of 97.66%. Antibacterial activity of silver nanoparticles was indicated by the formation of inhibition against the growth of Staphylococcus aureus bacteria with a clear zone formed around 12.091 mm. Therefore, the antibacterial inhibition formed from the silver nanoparticles synthesized in this study can be classified as a strong antibacterial property.